Helminths infecting Mabuya dorsivittata (Lacertilia, Scincidae) from a high-altitude habitat in Itatiaia National Park, Rio de Janeiro State, Southeastern Brazil - Rocha,C. F. D. (2003)
We analysed the helminth fauna associated with the lizard Mabuya dorsivittata (Scincidae) from a high-altitude area in Itatiaia National Park, Rio de Janeiro State, Brazil. Of the 16 lizards examined, 12 (75%) were infected by at least one helminth. Only two helminth species were found: Physaloptera retusa and Skrjabinodon spinosulus (Nematoda), the former with a prevalence of 68.8% and a mean infection intensity of 3.6 ± 2.8 and the latter with a prevalence of 56.3% and a mean infection intensity of 2.6 ± 2.6. The helminth fauna of the studied population of Mabuya dorsivittata was considerably poorer than those of other previously studied populations of congeners.